Utilization Of Information Technology And Change Management In Umkm After The Covid-19 Pandemic In Sharia - Widiyani Hasibuan (Jurnal Fokus Manajemen, 2023)
The purpose of this study is to determine how management changes the use of information technology to support the sustainability of small and medium enterprises during the COVID-19 pandemic. Information Technology and MP play a very important role in the management of the Covid-19 pandemic because Information Technology plays a role in managing information only for that time. MP offers structured only for individuals to bring their organizations into the desired current state. The task of Change Management is to identify groups and individuals who need change. In addition, Change Management requires the development of specific plans for only successful implementation of change. The first goal of Change Management is to provide a smooth and successful transition.